Biomass waste as a renewable energy in developing bio-based economies in Indonesia: A review. (May 2022) - Yana, Syaifuddin; Nizar, Muhammad; Irhamni,; Mulyati, Dewi
Abstract: The pressure on the government to use renewable energy sources as a future substitute for fossil fuels has prompted it to pursue alternative energy sources. Biomass has considerable potential as a renewable energy source in Indonesia. However, several barriers remain in relation to the application and development of biomass-based energy, including the concurrent use of biomass sources, such as CPO converted to stearin, for example, as a biofuel feedstock. Excluding the biodiesel industry, stearin is required by various large industries, including the oleochemicals, food, and cosmetics sectors. This situation results in competition and a conflict of interest among these industries. Furthermore, issues persist, for instance, plentiful forest fires and illegal logging. This situation has a significant impact on the loss of biomass sources. Conversely, the Covid-19 pandemic has impacted the global economy, reducing global energy demand, delaying the development of renewable energy priorities, in addition to placing the attainment of the national energy mix at risk. This study contributes to a greater understanding of the implementation, constraints, and challenges, as well as regulations associated with converting biomass to renewable energy and meeting the 2025 energy mix target. Highlights: Barriers to implementing and developing biomass as a renewable energy source. A critical review of developing biomass as renewable energy with emphases of challenge and conflict was presented. Competing interests in agriculture, plantations, and forest products, which can disrupt energy policy and impact energy development. Covid 19 pandemic impact economic growth and the achievement of the 2025 energy mix were presented. The constraints and challenges regulation and the government's strategy to accelerate the achievement of the 2025 energy mix were presented.